Enhancement of out-of-plane spin-orbit torque by interfacial modification - Zhao, Tieyang (2023)
Spin-orbit torque (SOT)-induced switching of perpendicular magnetization in the absence of magnetic field is crucial for the application of SOT-based spintronic devices. Recent works have demonstrated that the low-symmetry crystal structure in CuPt/CoPt can give rise to an out-of-plane (OOP) spin torque and lead to deterministic magnetization switching without an external field. However, it is essential to improve OOP effective field for the efficient switching. In this work, the impact of interface oxidation on the generation of OOP effective field in a CuPt/ferromagnet heterostructure is systematically studied. By introducing an oxidized CuPt surface, it is found that the field-free switching performance shows remarkable improvement. OOP effective field measurement indicates that the oxidation treatment can enhance the OOP effective field by more than two times. It is also demonstrated that this oxidation-induced OOP SOT efficiency enhancement is independent of the device shapes, magnetic materials, or magnetization easy axis. This work contributes to improve the performance of SOT devices and provides an effective fabrication guidance for future spintronic devices that utilize OOP SOT.